Prognosis of extracolonic findings on clinical computed tomographic colonography: A single-center experience. - Hideto Tomimatsu; Keita Fujimoto; Taketo Suto; Masayuki Matsuo (PLoS ONE)
Computed tomographic colonography (CTC) is crucial for colorectal cancer screening and secondary examinations, often revealing extracolonic findings with unclear significance. This study retrospectively evaluated the impact of such findings on the prognosis and management of 103 patients (mean observation period [OP]: 2183 days), categorized according to the CT Colonography Reporting and Data System (C-RADS). The distributions were 17% (mean OP: 2,821 days) for E1, 38% for E2 (2,759 days), 6% for E3 (2,150 days), and 39% for E4 (1,338 days). Eighteen patients were further examined, but no treatment-related changes were observed in the E2 or E3 cases. Six of nine E4 patients responded to treatment (mean OP: 1,286 days). Kaplan-Meier analysis revealed worse prognosis for E4 (mean survival: 10.1 years) than for E1-E3 combined (5.6 years) (p < 0.0001). E4 findings are key in guiding treatment. The concordance rate between the clinical (Past E) and revised (Revised E) categories was high (0.83, 95% confidence interval: 0.77-0.88). The prognoses differed significantly between Revised E1-E3 (mean survival: 10.0 years) and Revised E4 (6.2 years) (p < 0.0001). Although E4 significantly affects prognosis, E2 and E3 had limited effects on treatment, highlighting the need for further study to improve diagnostic accuracy.